2004
DOI: 10.1063/1.1836878
|View full text |Cite
|
Sign up to set email alerts
|

Metal/semiconductor phase transition in chromium nitride(001) grown by rf-plasma-assisted molecular-beam epitaxy

Abstract: Structural and electronic properties of stoichiometric single-phase CrN(001) thin films grown on MgO(001) substrates by radio-frequency N plasma-assisted molecular-beam epitaxy, are investigated. In situ room-temperature scanning tunneling microscopy clearly shows the 1 ϫ 1 atomic periodicity of the crystal structure as well as long-range topographic distortions which are characteristic of a semiconductor surface. This semiconductor behavior is consistent with ex situ resistivity measurements over the range 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
81
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 17 publications
20
81
4
1
Order By: Relevance
“…As for semiconducting properties, previous reports have announced different band gaps for CrN. Constantin et al [12] prepared 1:1 stoichiometric CrN thin films deposited by molecular beam epitaxy, and reported a resistivity-derived 71 meV band gap at room temperature, by using the ln(ρ/ρ 0 ) = (E g /2k B )(1/T) equation which relates the resistivity of a semiconductor to ambient temperature and the energy band gap where ρ is the electrical resistivity, ρ 0 is the resistivity pre-factor, E g is the semiconductor band gap, k B is the Boltzmann constant and T is temperature. Zhang et al [13] measured the optical properties of CrN and concluded that the band gap is 0.19 eV with an error bar of 0.46 eV, demonstrating difficulties in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…As for semiconducting properties, previous reports have announced different band gaps for CrN. Constantin et al [12] prepared 1:1 stoichiometric CrN thin films deposited by molecular beam epitaxy, and reported a resistivity-derived 71 meV band gap at room temperature, by using the ln(ρ/ρ 0 ) = (E g /2k B )(1/T) equation which relates the resistivity of a semiconductor to ambient temperature and the energy band gap where ρ is the electrical resistivity, ρ 0 is the resistivity pre-factor, E g is the semiconductor band gap, k B is the Boltzmann constant and T is temperature. Zhang et al [13] measured the optical properties of CrN and concluded that the band gap is 0.19 eV with an error bar of 0.46 eV, demonstrating difficulties in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Considerable experimental and theoretical work have demonstrated that CrN undergoes a magnetic and structural phase transition from a paramagnetic NaCl structure at room temperature to a low-temperature antiferromagnetic orthorhombic P nma phase at N eel temperature of 273-286 K. [5][6][7] A variety of electrical transport properties in CrN have been observed, such as, a semiconducting behavior with dq/dT < 0, [8][9][10][11] a metallic behavior with dq/dT > 0, [12][13][14] and continuous and discontinuous q(T) curves at 260-280 K. [8][9][10][11][12][13]15 These differences in electrical transport properties have been attributed to the sensitivity of the transport properties to N stoichiometry. 12,15 In addition, the discontinuity in q(T) curves has usually been observed in CrN powders or polycrystalline CrN films, rather than in epitaxial films, suggesting that the epitaxial constraints could affect the transition.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Electronic transport studies report controversial results for CrN, including (i) values for the resistivity ρ at room temperature range over more than two orders of magnitudes, from 1.7×10 -3 to 3.5×10 -1 Ωcm, 3,[5][6][7][8][9][10] even when only considering the most reliable data for single crystal CrN layers; (ii) the temperature dependence of ρ shows metallic behavior with dρ/dT > 0 in some studies, 6,7,11 but an increase in ρ with decreasing temperature in other reports, 3,5,9,12 which has been attributed to the presence of a band gap 5 or carrier localization due to crystalline defects 13 or N-vacancies; 14 (iii) some studies report a discontinuity in ρ(T) at 260-280 K, 3,6,7,14 which is associated with a magnetic and structural phase transition from a paramagnetic NaCl structure at room temperature to a low-temperature antiferromagnetic orthorhombic P nma phase 11,15 with a 0.56-0.59% higher density, 11 and a 25% lower bulk modulus, 16 while other reports show no evidence for a phase transition in the ρ(T)-curves. 5,7,9 Electronic structure calculations suggest that magnetic stress relief couples magnetic ordering with the structural phase transition, 17 and that CrN exhibits a band gap if the Hubbard Coulomb interaction term is sufficiently large.…”
mentioning
confidence: 99%